Optimization of Mass Reconstruction Algorithm for Atom Probe Tomography Analysis - Shutov, A. S.; Lukyanchuk, A. A.; Rogozhkin, S. V.; Raznitsyn, O. A.; Nikitin, A. A.; Aleev, A. A.; Kirillov, S. E. (Physics of atomic nuclei, 2019)
Atom probe tomography (ATP) is a technique that has actively been developed in recent years. This method allows one to investigate three-dimensional distributions of chemical elements in various materials with atomic spatial resolution. The raw APT data reconstruction algorithm uses the geometry of evaporated ion trajectories. However, the basic algorithm uses the approximation of rectilinear trajectories of ions moving from the specimen to the detector. In this study, we present the main approaches to adapting and optimizing the basic APT data reconstruction algorithm concerning the mass reconstruction procedure. Methods for taking into account the nonlinear distortions of ion trajectories due to the wide-angle detection system and other features of ion detection in atom probe tomography are demonstrated. Using a titanium alloy (Ti—5Al—2.7Mo—2Zr), we demonstrate that the consideration of the above effects in the reconstruction of ATP data makes it possible to increase the mass resolution, m /Δ m 50% , of the main peaks of the mass spectrum to 600 and above. In general, the set of performed procedures allows one to achieve a high accuracy of the positioning of the peaks up to 0.01 amu and ensures a significant (more than tenfold) increase in the mass resolution for mass spectrum peaks that are distant from the main peaks.